Uma articulação entre Castoriadis e Lefebvre - Alexandre Mesquita Silva Bomfim (2019)
This dissertation studies the concept of spatial imaginary through the articulation between Cornelius Castoriadis and Henri Lefebvre. Castoriadis affirms that society is imaginarily instituted from a matrix of meaning instituted by that same society. Lefebvre proposes that social space is the manifestation of social relations. This study, then, postulates that society, which is the set of instituted social relations, institutes itself imaginatively and manifests itself in social space based on an interpretative matrix of reality that gives meaning to both established social relations and its manifestation in social space: the spatial imaginary. The latter is a socially shared way of making sense of reality by ordering it in social institutions, social relations, and social space. Considering the relevance of the concept and the very varied treatment that is dedicated to it, this research sought to elaborate it from the theoretical frameworks chosen. It is believed that, based on the joint reading of Castoriadis and Lefebvre, it is possible to affirm that the way in which society establishes its social and spatial practices is only one possible way, but not the only one. After this, through the analysis of some experiments considering the concept of spatial imaginary elaborated here, this work presents signs of this imaginary and analyzes it within the notions of heteronomy and autonomy. It is assumed that the alleged 'naturalness' with which society understands the production of itself and its space is a trait of heteronomy and is related to the autonomization of the imaginary moment of its institution. This autonomization would mask the fact that the spatial imaginary instituted is a social construction that can be transformed. It is proposed, therefore, that the autonomization of an already established spatial imaginary is an obstacle to the practice of autonomy by society, hindering the modification of itself, which hampers the achievement of social justice and the promotion of quality of life, achievable by the openness of society to permanent selfinstitution. In the end, it is suggested that it is the task of architects and urban planners to create instruments that help society to exercise its autonomy over the production of its own space and the institution of its social relations.